2018
DOI: 10.3389/fnins.2018.00710
|View full text |Cite
|
Sign up to set email alerts
|

The Attentional Suppressive Surround: Eccentricity, Location-Based and Feature-Based Effects and Interactions

Abstract: The Selective Tuning model of visual attention (Tsotsos, 1990) has proposed that the focus of attention is surrounded by an inhibitory zone, eliciting a center-surround attentional distribution. This attentional suppressive surround inhibits irrelevant information which is located close to attended information in physical space (e.g., Cutzu and Tsotsos, 2003; Hopf et al., 2010) or in feature space (e.g., Tombu and Tsotsos, 2008; Störmer and Alvarez, 2014; Bartsch et al., 2017). In Experiment 1, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 70 publications
3
11
0
Order By: Relevance
“…For short SRTs, there were no statistically significant differences between similarity levels when examining the angle and curvature metrics over increasing OS (as the objects became less similar). However, there was a significant DoG-shaped pattern for endpoint deviation, consistent with a non-spatial suppressive surround, found for simple features such as color, orientation, and direction of motion (Tsotsos et al, 2005;Tombu and Tsotsos, 2008;Störmer and Alvarez, 2014;Yoo et al 2018;Kehoe et al, 2018b). Our results show, for the first time, an object-based suppressive surround active during the discrimination phase of target-distractor competition.…”
Section: Effects Of Similarity On Saccade Trajectoriessupporting
confidence: 86%
“…For short SRTs, there were no statistically significant differences between similarity levels when examining the angle and curvature metrics over increasing OS (as the objects became less similar). However, there was a significant DoG-shaped pattern for endpoint deviation, consistent with a non-spatial suppressive surround, found for simple features such as color, orientation, and direction of motion (Tsotsos et al, 2005;Tombu and Tsotsos, 2008;Störmer and Alvarez, 2014;Yoo et al 2018;Kehoe et al, 2018b). Our results show, for the first time, an object-based suppressive surround active during the discrimination phase of target-distractor competition.…”
Section: Effects Of Similarity On Saccade Trajectoriessupporting
confidence: 86%
“…This interpretation suggests that feature-based attention might interact with spatial attention (spatial attention refers to the allocation of attention to spatial locations, while feature-based attention refers to the allocation of attention to different features independently of their spatial locations). Our previous study provided supporting evidence for the interaction between spatial and feature-based surround suppression [35]. We showed that the suppressive effect is greatest when the two (spatially) adjacent targets are also close in feature space.…”
Section: Effects Of Feature-based Attention On Motion Direction Tunin...supporting
confidence: 67%
“…p = 0.017, BH critical value = 0.013). To provide converging evidence, we fit a quadratic model to the data as an approximation of the surround suppression [ 35 ] and compared its goodness-of-fit with that of a linear model. Whereas the linear model did not properly fit the data (adjusted R 2 = − 0.305, AIC = 11.344), the quadratic model, an approximation of the surround suppression [ 35 ], showed a better fit (adjusted R 2 = 0.734, AIC = 6.826).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that changes in spatial attention, rather than memory load accounted better for memory performance. Attended regions can have inhibitory surrounds [ 58 , 59 ], and crowding is also known to occur when distractor items approach attended items [ 60 , 61 ]. In spite of these characteristics of attention, we modeled the effects of attention as a single Gaussian distribution because we modeled behavioral data that were averaged across many trials.…”
Section: Materials and Methodsmentioning
confidence: 99%